Supplemental trace minerals (zinc, copper, and manganese) as sulfates, organic amino acid complexes, or hydroxy trace-mineral sources for shipping-stressed calves - Ryan, A.W. (Prof Anim Sci, 2015)
Crossbred calves (n = 350; average BW 240 ± 1 kg) were obtained from regional livestock auctions. Within each set (block, n = 4), calves were stratified by BW and arrival sex into 1 of 8, 0.42-ha pens (10 to 12 calves per pen). Pens were assigned randomly to 1 of 3 treatments consisting of supplemental Zn (360 mg/d), Mn (200 mg/d), and Cu (125 mg/d) from inorganic (zinc sulfate, manganese sulfate, and copper sulfate; n = 2 pens per block), organic (zinc amino acid complex, manganese amino acid complex, and copper amino acid complex; Availa-4, Zinpro Corp., Eden Prairie, MN; n = 3 pens per block), and hydroxy (IntelliBond Z, IntelliBond C, and IntelliBond M; Micronutrients, Indianapolis, IN; n = 3 pens per block) sources. During the 42- to 45-d backgrounding period calves had ad libitum access to bermudagrass hay and were fed corn and dried distillers grain–based supplements that served as carrier for the treatments. After removal of data for chronic (n = 6) and deceased (n = 1) calves, trace-mineral source had no effect on final or intermediate BW (P = 0.86) or ADG (P ≥ 0.24). With all data included in the analysis, dietary treatments had no effect on the number treated once (P = 0.93), twice (P = 0.71), or 3 times (P = 0.53) for bovine respiratory disease or on the number of calves classified as chronic (P = 0.55). Based on these results, trace-mineral source had no effect on total BW gain, ADG, or morbidity during the receiving phase in shipping-stressed cattle.